수익형 민간투자사업(BTO) 입찰평가 분석: 도로사업을 중심으로 - 김정욱 (12230, 2011)
Upon selecting preferred bidder in Public-Private Partnership projects, multi-dimensional procurement auction, where price factor and non-price factor are evaluated, is used. This paper tries to analyze bidding data in BTO road projects. It is shown that